Chances of Early School Leaving-With Special Regard to the Impact of Roma Identity - Veronika Bocsi; Aranka Varga; Anikó Fehérvári (MDPI AG, 2023)
Early school leaving rates among Roma are higher than in the majority population, as confirmed by several studies, but the descriptions are often two-dimensional. Intersectionality is described as a persistent situation formed by several social dimensions, and this specific position can be advantageous or disadvantageous from the aspect of educational inequalities. This study aims to explore what type of intersectional position can raise the chance of early school leaving and what is the role of the Roma ethnic identity in this. Earlier empirical analyses are rather two-dimensional, and these intersectional situations cannot be identified with them. The Hungarian Youth Survey databases provided an opportunity to conduct this type of multiple approaches. With the help of our results, the intersectional position can be described in which the chance of early school leaving is higher. The elements of this situation are embedded in economic, educational, geographical and ethnic categories at the same time. The effect of Roma ethnic identity is significant but not the strongest in our model. With the help of a comparison of the two waves of the research project, we can state that the patterns of this intersectional and disadvantageous situation are stable but not unchanged.